DEVELOPMENT OF COMIC LEARNING MEDIA TO IMPROVE STUDENT’S CONCEPT UNDERSTANDING AND LEARNING INDEPENDENCE - Laili Ulviah; Salamun Hadi Subroto; Oriza Satifah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This research aims to produce learning media in the form of science comic that can improve conceptual understanding and learning independence of class VI students. This development research adapts the development of 4- D model media, but only until the Develop stage. The trial design carried out is the validation test of material experts and media experts as well as teachers, limited trials and field trials. The data collection instruments use questionnaires, question sheets and validation sheets to obtain qualitative and quantitative data. The questionnaires and questions used to collect the data are also validated first. The results show that the media developed by experts is in the